ISO 9000 maintenance measures: the case of a Malaysian local authority - Basir, Siti Arni; Davies, John (Taylor & Francis, 2018)
Although many studies pertaining to ISO 9000 initiatives have been conducted, the topic of ISO 9000 maintenance has received little attention from researchers. This paper presents a detailed case study of the ISO 9000 maintenance measures within a Malaysian local authority. Semi-structured interviews were conducted with 15 interviewees. The findings revealed that six measures are undertaken in ISO 9000 maintenance; namely, control of documents, internal quality audit, data analysis and feedback, management review, corrective and preventative action and training. The research findings also revealed that the ISO 9000 maintenance measures are effectively carried out at a Malaysian local authority in this study. Although adherence to work procedures and focus on customer satisfaction have been given priority, the ISO 9000 maintenance has progressed into a more advanced phase by making ISO 9000 a tool to deliver a high-quality service that results in organisational performance improvement. Continuous improvement initiatives have enabled ISO 9000 maintenance to move forward and reach its advanced stage. The findings derived from this research would facilitate managers to understand the measures needed for effective ISO 9000 maintenance. The main contribution of this study is that it is one of the first to explore ISO 9000 maintenance in a specific sector, that is, local authority. Hence, the findings are significantly important in developing the knowledge of ISO 9000 maintenance in the local authority sector.